PENGEMBANGAN BAHAN AJAR DENGAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) UNTUK MEMFASILITASI PENCAPAIAN KEMAMPUAN PEMAHAMAN DAN PENALARAN MATEMATIS SISWA SEKOLAH DASAR - Desilia Elisabet; Agung Hartoyo; Yulis Jamiah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This study proposes the development of teaching materials with the RME approach to facilitate the achievement of elementary school students' mathematical understanding and reasoning abilities. The purpose of this research is the compilation of teaching materials with the RME approach that can be used to facilitate the achievement of valid, practical, and effective students' mathematical understanding and reasoning abilities. The method used in this research is the method of development (R&D). This research is a development research that uses the ADDIE development model. The ADDIE development model consists of five steps, namely Analysis, Design, Development, Implementation, and Evaluation. This research produces valid, practical and effective teaching materials that can be used to facilitate the achievement of students' mathematical understanding and reasoning. Valid teaching materials are seen from the validity of teaching materials, practical teaching materials seen from the results of observations of module implementation during learning effective teaching materials seen from the observations of the teacher's ability to manage learning, student activities, student response questionnaires, and student learning outcomes tests. Keywords: Teaching Materials Development, Realistic Mathematics Education, Mathematical Understanding and Reasoning